Use of Genetic Algorithm on Optimal Power Flow: An Illustration of Transmission Line Loss Minimization - Lamichhane, Bishal; Luintel, Mahesh Chandra (Kathford Journal of Engineering and Management, 2018)
This paper presents the usefulness and effectiveness of Genetic Algorithm on solving Optimal Power Flow (OPF) problem formulation of a real world power system. Optimization is a broad concept that is generally directly or indirectly related to cost factor. In this case, transmission lines loss minimization is presented as the objective of optimization problem formulation keeping all other technical factors and parameters under operating constraints. Results of this study, presented in the Integrated Nepal Power System (INPS) transmission line network show that the Genetic Algorithm is effective method to optimize the power flow via assigned objective of transmission loss minimization in much quicker and effective way when compared to conventional Newton-Rapshon method.